The Role of Severus Snape in The Harry Potter Series by J. K. Rowling: Deconstruction Perspective - Melliandhini, Hayyu Afifah; Kurniawati, Neni (Allure Journal, 2024)
This paper aims to find out the real role of Severus Snape in the Harry Potter book series by J. K. Rowling. This research is also intended to describe Severus Snape's efforts in defeating Lord Voldemort as well as to figure out the characterization and description of the actions taken by Snape; the writer uses a deconstruction analysis proposed by Jacques Derrida. The image of Severus Snape's character and the relationship between the character's image and the forms of deconstruction are identified by the deconstruction analysis. The method used in this research is the descriptive qualitative method. This research tried to examine the elements of deconstruction of the character Severus Snape in the Harry Potter series of novels, interpreting the new meanings contained implicitly in the novels. The results of the research showed that Severus Snape is described as a character who is rude, arrogant, and cruel. Through the perspective of deconstruction, it was found that Snape has characteristics that are paradoxical to what appears on the surface. He is a caring, helpful, and brave character. In addition, it was found that nine actions of Severus Snape were intended to protect Harry Potter and to defeat Lord Voldemort. The results of the analysis suggested that Severus Snape has a significant role in moving the story. Through his role in the story, Harry Potter can defeat the antagonist or villain in the Harry Potter Series.